BONDS OF PERFECT UNITY: Exegetical and Philosophical Approaches to Love, Mercy and Forgiveness - Bloechl, Jeffrey (Journal of Dharma, 2020)
Christian life centres on the practice of the virtues of faith, hope, and love. Love in turn informs mercy and forgiveness. These virtues are essentially communal, and their fulfilment is withheld until the Second Coming of Jesus. Together, this means that Christian life is a shared life in which the essential practices bind the members together in the presence of Jesus Christ. These claims are developed on the basis of a reading of Chapter 3 of the Letter to the Colossians. The reading is at once exegetical insofar as attention is paid to the Greek text and the author’s historical-cultural context, and philosophical insofar as certain key concepts and phenomena are drawn from the theology of the Letter. What exegesis proposes to the life of faith, philosophy is able to disclose in its objective meaning.